Take AIM and Keep Your Students Engaged - Catherine Theresa Mary Nash (Flexible Learning Association of New Zealand, 2014)
This paper outlines the benefits to distance education teachers of formatting a weekly online newsletter in accordance with motivational learning theory. It reflects on the delivery of weekly AIM newsletters to undergraduate economics students at the Open Polytechnic of New Zealand via Moodle. The acronym, AIM, stands for Academic content, Information for the course and Motivation-three critical elements required to meet the challenges of effective course facilitation. The AIM newsletter integrates all three of these key components in one easy-to-use product. The object of AIM is to keep students engaged in economics and reduce the perceived distance from distance education. This article discusses the context, underpinning theory, practicalities, and the way forward for AIM.